Routing and wavelength assignment for WDM-based optical networks : quality-of-service and fault resilience /: quality-of-service and fault resilience. (2016) - Chatterjee, Bijoy Chand; Sarma, Nityananda; (Writer on optical networks), Sahu, Partha Pratim; Oki, Eiji, 1969-
No abstract available